AN ANALYSIS ON JARGON USED IN INDONESIA LAWAK KLUB (ILK) PROGRAM ON TRANS 7 - Yuli Astutik (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2016)
This research aims to analyze the jargon used in Indonesia Lawak Klub (ILK) program on Trans 7. The problems formulated are: 1) What are the jargons and types of jargon used in Indonesia Lawak Klub (ILK) program on Trans 7?, 2) What is the dominant type of jargon used in Indonesia Lawak Klub (ILK) program on Trans 7?. The method used in this research was descriptive qualitative design. In applying this method, the writer used the technique of observation because the writer wanted to pay attention, watch and listen carefully to the sources of the data. The writer also observed the conversation that occurred among the entertainers in ILK program by using video and tape recorder. After conducted the observation on the date of 12, 13 and 20 of October 2015, the result showed that there were 37 (100%) jargons used by the comedians and the guest in ILK program on Trans 7 when they talked with each other. Then, there were three types of jargon used in this program such as 24 (64, 86%) abbreviations, 11 (29, 72%) deviation words and 2 (5, 4%) deviation names. The most dominant type of jargon used in Indonesia Lawak Klub (ILK) program was abbreviation.